Pengaruh Love Of Money dan Family Conditions terhadap Minat Berwirausaha dengan Dukungan Religius Sebagai Variabel Mediasi dalam Prespektif Bisnis Islam (Studi Pada Masyarakat Nelayan di Kelurahan Kangkung, Kecamatan Teluk Betung Selatan, Bandar Lampung) - Agung Frasetya; Hanif; Agus Kurniawan (MES Management Journal, 2025)
This study aims to analyze the influence of Love of Money and Family Conditions on Entrepreneurial Interest with Religious Support as a Mediating Variable from an Islamic Business Perspective in the Fishermen Community in Kangkung Village, South Teluk Betung District, Bandar Lampung. The research was conducted considering the low interest in entrepreneurship among the fishing community, where the majority (78%) of the 50 pre-survey respondents were not interested in entrepreneurship. The research uses a quantitative approach with a survey method. The research population is the fishing community in Kangkung Village, with the sample determined based on specific criteria. The research variables include Love of Money and Family Conditions as independent variables, Entrepreneurial Interest as the dependent variable, and Religious Support as the mediating variable. The data collection technique uses a questionnaire with a measurement scale. Data analysis was conducted using the Partial Least Square (PLS) approach to test the relationships between variables and the mediating role of Religious Support. The research results are expected to provide theoretical contributions in understanding the factors that influence entrepreneurial interest among fishing communities, as well as practical contributions in the form of recommendations for economic empowerment strategies based on the Islamic business perspective.